2015
DOI: 10.4236/ajmb.2015.52005
|View full text |Cite
|
Sign up to set email alerts
|

Inteins—A Focus on the Biotechnological Applications of Splicing-Promoting Proteins

Abstract: The main aim of this mini-review is to illustrate strategies and industrial applications based on inteins (INTErnal proteINS), which belong to a class of autocatalytic enzymes that are able to perform a catalytic reaction on a single substrate. However, since practical applications of inteins are strongly guided by a detailed understanding of their biological mechanisms and functions, the first part of this review will thus briefly discuss the physiological roles of inteins, describing what is currently known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 106 publications
0
4
0
1
Order By: Relevance
“…Although long considered nothing more than the products of parasitic genetic elements (3), recent work has shown that some inteins function as environmental sensors to modulate host protein function in response to environmental changes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Identifying cellular or environmental factors that influence intein splicing, and thus regulation of essential protein functions, is an emerging area of interest in both basic and applied research fields (16)(17)(18).…”
mentioning
confidence: 99%
“…Although long considered nothing more than the products of parasitic genetic elements (3), recent work has shown that some inteins function as environmental sensors to modulate host protein function in response to environmental changes (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Identifying cellular or environmental factors that influence intein splicing, and thus regulation of essential protein functions, is an emerging area of interest in both basic and applied research fields (16)(17)(18).…”
mentioning
confidence: 99%
“…The amino acid residue at position +1 consists either of a cysteine, serine, or threonine, depending on the split intein. PTS takes place in four steps: (1) a nucleophilic attack by the first amino acid residue of either a cysteine or serine located in the N-terminal intein part on the carbonyl carbon of the preceding amino acid residue (−1 position) located in the flanking N-extein leads to an N-S or N-O acyl shift; (2) a linear (thio) ester intermediate being trans-esterificated by a nucleophilic attack of the first amino acid residue of the so-called C-extein (+1 position) forms a branched intermediate [95]; (3) the N-terminal intein part is now cleaved from its fusion protein and transferred to the N-extein. As a result, a succinimide ring is generated through cyclization of the conserved asparagine residue of the C-terminal intein part after the nucleophilic attack of the previously formed intein extein junction; (4) finally, the cleavage reaction of the C-terminal intein part followed by a spontaneous S-N or O-N acyl shift ligates the esterified C-and N-exteins by a native stable peptide bond [96,97].…”
Section: Split Inteinsmentioning
confidence: 99%
“…İnteinlerin kendiliğinden proteinden ayrılma özelliğinin belirlenmesi ile birlikte inteinler protein saflaştırmasında kullanılmaya başlanmıştır. İnteinler herhangi bir polipeptitten kimyasal olarak ayrılabilme veya peptitleri birbirine bağlayabilme özelliklerinden dolayı birçok moleküler çalışmada kullanılmaktadırlar [8][9][10][11]. Doğal halde organizmalarda bulunan inteinler ilk defa Saccharomyces cerevisiae VMA1 geninden elde edilmiştir [12,13].…”
Section: İntei̇nunclassified